2016
DOI: 10.1109/tvt.2015.2422715
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Cyclostationary-Based Cooperative Sensing Using Field Measurements

Abstract: This paper focuses on evaluating the gains obtained through cooperative spectrum sensing in real-world while using cyclostationary based mobile sensors. In cooperative sensing (CS), different secondary users (SUs) in a geographical neighborhood cooperate to detect the presence of a primary user (PU). As compared to single-user sensing, cooperation provides diversity gains in the face of multipath fading and shadowing. The effectiveness of the CS is demonstrated by analyzing data acquired in two extensive field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In our experiments we have used measured data to construct the spectral maps for different frequencies. The measurements are from DVB-T network, see [12]. For the radars, we placed three radars with 90 deg scanning sectors in the area.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In our experiments we have used measured data to construct the spectral maps for different frequencies. The measurements are from DVB-T network, see [12]. For the radars, we placed three radars with 90 deg scanning sectors in the area.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Moreover, the authors in the aforementioned works analyzed the temporal characteristics of the PU activity. In the work of Chaudhari et al, it has been proven that a measurement‐based spatial interpolation approach is more accurate than the DBA approach for constructing an REM. A cooperative SS using the Kriged Kalman filtering has been used in the work of Kim et al, and a notion of channel gain maps has been introduced, thereby proving the necessity of a spatio‐temporal channel correlation structure for estimating the REM.…”
Section: Related Work Motivation and Contributionmentioning
confidence: 99%
“…In the reporting step, SUs forward their observations or local decisions to the fusion center (FC). In the decision phase, FC makes a global decision about the presence or the absence of primary users based on the collected local observations by using a hard or a soft combining scheme [11,12,13,14]. The authors in [15] have shown the criteria for an effective decision approach selection analytically with high detection accuracy as an objective in the presence of realistic channel propagation effects for two different decision approaches as combining decision (CD) and sensing and combining decision (SCD).…”
Section: Introductionmentioning
confidence: 99%